Preparation of zinc oxide nanopowders doped with manganese, which have ferromagnetic properties at room temperature - Vorovsky, V.Yu.; Kovalenko, A.V.; Kushneryov, A.I.; Khmelenko, O.V. (Functional Materials, 2018)
The paper analyzes magnetic properties, crystal structure and EPR spectra of ZnO:Mn nanocrystals obtained by ultrasonic spray pyrolysis. It has been investigated influence of the type of carrier gas - air and nitrogen on the magnetic properties of the nanocrystals at room temperature. Also it has been investigated effect of heat treatment at T = 800°C and phase of Mn₂O₃ presented in the nanocrystals of ZnO:Mn, on the magnetic properties.